DARWIN AND RELIGIOCITY (On the occasion of World Darwin Day) - Athanasiou, Kyriacos (EFSYN, 2020)
Darwin's Day has been celebrated, worldwide, a few weeks ago. This communication does not intend to address Darwin's scientific views, but aims to focus on his religious beliefs and, above all, on the reasons why Darwin was led to reject religion. Which, in the opinion of the writer, it is not related to his scientific views, i.e. the Theory of Evolution through Natural Selection but, mainly, with reasons that go back to the field of Ethics in the broad sense, and to logical considerations, as well.